Left Insular Low-Grade Glioma: A Rare Comprehensive Case Report - V.G, Sapthami Ramya; Dharshini, Deva; A.G, Charanya; K, Shailaja (Indian Journal of Pharmacy Practice)
Low-Grade Gliomas (LGGs) are a specific type of brain tumor that are characterized by slow-growing, less aggressive cancerous cells that originate from glial cells, which support and protect neurons in the brain and spinal cord. The insula is a small region of the cerebral cortex located deep within the lateral sulcus, and tumors in this area are particularly challenging to treat due to the critical functions it supports, such as language, sensory processing, and autonomic control. Left Insular Low-Grade Gliomas (LILGGs) are a rare and particularly complex form of LGG. Although these tumors grow slowly, they have the potential to become malignant over time. They arise from neuroepithelial tissue and are derived from glial cells. Despite their rarity, LILGGs are well-documented in medical literature. This case report discusses a 50-year-old female patient diagnosed with a left insular low-grade glioma. The patient presented with symptoms that warranted further investigation, leading to the diagnosis of this uncommon tumor. The detailed analysis of her case adds to the existing body of knowledge, providing insights into the presentation, diagnosis, and potential treatment approaches for this rare and challenging condition.
Keywords: Case Report; Left Insular Low-Grade Glioma; Brain Tumour; Rare Cerebral Cancer